MANAJEMEN KEGIATAN EKSTRAKURIKULER BERBASIS PENGEMBANGAN KARAKTER SISWA - Romadon Taufik (Manajer Pendididikan, 2015)
This study aims at describing the mangement of students’character development based extracurricular activity. This study used qualitative descriptive method. The subject of this study consists of the school principal, the vices of school principles, the teachers, and the students. The data were collected by means of observation, interview, and documentation. Afterwards, the data were analized by using the technique as proposed by Miles and Huberman. The result of this study shows that the students’ character development based extracurriculer activity has been conducted based on the principles of effective management involving the processes of planning, organizing, actuating, evaluating, and controlling.Keyword: management, extracurricular, development, student character